Broadband wide-area networking via IP - Farserotu, J.
A concept for broadband wide-area networking based on the use of the Internet Protocol (IP) over asynchronous transfer mode (ATM) broadcast over extremely high-frequency (EHF) 30/20 GHz Ka-band satellite communication (SATCOM) is presented. It is primarily intended to support applications such as broadcast of data and video, fast Internet access, and teleconsultation with interactive white board. Operation from midsize terminals located at a corporate headquarters to small highly transportable terminals at remote facilities is envisioned
Keywords: 20 GHz; 30 GHz; ATM broadcast; EHF; IP/ATM.; Internet Protocol; WAN; Asynchronous transfer mode; Broadband wide-area networking; Data broadcasting; Extremely high-frequency.; Fast Internet access; Interactive white board; Remote facilities; Satcom; Satellite communication; Teleconsultation; Transportable terminals; Video broadcasting